The Role of Chemistry in Environmental Education: Learning and Constructing Knowledge Through Research in High School - Arthur Inocencio Borges; Mayker Lazaro Dantas Miranda (Indonesian Journal Of Educational Research and Review, 2022)
Preservation, conservation, sustainable development, and quality of life should become part of everyday life for people worldwide. Chemistry teachers should discuss environmental issues with students directly and take the opportunity to promote emancipatory Environmental Education, enabling students to live in harmony with the environment. The first aim of this research is to investigate how Environmental Education in teaching chemistry can shape citizens who are critical of environmental issues. This type of qualitative research uses a participatory action research approach to describe reality and is more concerned with the process than the product. The methods used in collecting data are observation, documentation, and questionnaires. The instrument used in collecting data is a questionnaire. The technique used to analyze the information is descriptive qualitative analysis. The result of the research is that the students express their perceptions about the environment and how human actions disturb nature globally. Individual accountability is becoming an essential objective for promoting a new model of development, which many refer to as sustainable development. In short, it is also proved that the insertion of Environmental Education in Chemistry class is essential for education and the social environment. It is because environmental education provides training to students and the entire school community on the importance of knowing environmental preservation mechanisms.